Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1029/2018ms001326
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Mountain Hydroclimate Simulations in Variable‐Resolution CESM to Microphysics and Horizontal Resolution

Abstract: Mountains are natural dams that impede atmospheric moisture transport and water towers that cool, condense, and store precipitation. They are essential in the western United States where precipitation is seasonal, and snowpack is needed to meet water demand. With anthropogenic climate change increasingly threatening mountain snowpack, there is a pressing need to better understand the driving climatological processes. However, the coarse resolution typical of modern global climate models renders them largely in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 101 publications
2
50
0
Order By: Relevance
“…Also, this lack of prognostic rainfall/snowfall could lead to an overestimation bias on the windward sides of the mountain ranges, particularly snowfall (even at 6‐km grids). Advection of droplets and snowflakes may have important effects on the fine‐scale distribution of snowpack for very high resolution simulations (Rhoades et al, ). Since our analysis is done at an aggregated HUC8 watershed scale, our results may not be very sensitive to cross‐grid advection of precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this lack of prognostic rainfall/snowfall could lead to an overestimation bias on the windward sides of the mountain ranges, particularly snowfall (even at 6‐km grids). Advection of droplets and snowflakes may have important effects on the fine‐scale distribution of snowpack for very high resolution simulations (Rhoades et al, ). Since our analysis is done at an aggregated HUC8 watershed scale, our results may not be very sensitive to cross‐grid advection of precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NA‐CORDEX ensemble only provides simulation data at 25‐ and 50‐km resolutions, coarser than generally preferred for mountain snowpack products (Ikeda et al, ; Letcher & Minder, ; Pavelsky et al, ; Wrzesien et al, ; Wrzesien et al, ), it is nonetheless a significant improvement over other multimodel ensembles such as the Coupled Model Intercomparison Project phase 5 (CMIP5) GCM ensemble. Further, it is at a sufficiently high resolution to still provide value for snowpack assessment when factoring in the important trade‐offs between model resolution, subgrid‐scale parameterizations, and global forcing data set (Rhoades, Ullrich, Zarzycki, et al, ; Xu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…This is an inappropriate assumption over areas for which the timescale of hydrometeor fallout is longer than the timescale for horizontal transport of hydrometeors across the model grid. Rhoades et al () found that precipitation biases over the California Mountainous Region are significantly improved in their VR‐CESM simulations with prognostic rain and snow treatment (Gettelman & Morrison, ), especially at model resolutions finer than 0.25°.…”
Section: Validation Of Cesm and Wrf Simulationsmentioning
confidence: 99%
“…Other studies have found their way around the resolution-computation conundrum by implementing variable resolution (VR) models to simulate climate phenomena (e.g., Fox-Rabinovitz et al, 2006;Harris & Lin, 2012, 2014Hourdin et al, 2006;McGregor, 1996;Sabin et al, 2013;Sakaguchi et al, 2015;Zhou & Li, 2002). Specifically, VR versions of CESM have been used to study tropical cyclones (Zarzycki et al, 2013;Zarzycki & Jablonowski, 2014), snowpack, and hydroclimate in the western United States Rhoades et al, 2016Rhoades et al, , 2018Wu et al, 2017Wu et al, , 2018Zarzycki et al, 2015) and to examine their capability for regional climate simulations (Gettelman et al, 2017). This process generally makes use of a "regional refinement" of the horizontal grid to very high horizontal resolutions of a domain of interest, which coarsens to large horizontal grid spacings away from the domain of interest.…”
Section: Introductionmentioning
confidence: 99%